Figurative Language in the Lyrics of Songs on Adele’s “21” Album - Ridhaswari Isnainingrum Fatihah; Rr. Astri Indriana Octavita; Agung Prasetyo (JEdu: Journal of English Education, 2022)
This study aims to find out what figurative language is contained in the song lyrics on Adele's "21" album. This study used descriptive qualitative method. In analyzing this research, the researcher uses the theory of figurative language style by Gorys Keraf (2010) and Nurgiyantoro (2009). The results of this study were dominated by 11 metaphors with a percentage (47.80%). While in the second position there are 8 hyperboles with a percentage (34.80%) and 4 personifications with a percentage (17.40%).